GLOBALISASI EKONOMI BISNIS - Ismail Nawawi (Maliyah : Jurnal Hukum Bisnis Islam, 2014)
Business economy globalization is a process in which the activities of countries around the world to be a power market is increasingly integrated with the country's territorial borders unimpeded. Results of this study that the real embodiment of the business in the form of economic globalization globalization of production, finance, labor, and globalization of trade information network. In the globalization of business competitive businessman making changes to the business with the support of the financial system and Islamic banking institutions. To encourage the positive impact businesses are not terlerpas of economics and business ethics, economic freedom, economic balance of business, issue and benefits, as well as justice berekonomi. And to mitigate the negative impacts in the business pembisnis avoid riba, gharar, gambling, and illicit Subhat. Usefulness of this research is the development of a competitive business theory and business people to be able to respond, and apply the results of this study in the economic life of the Islamic global business.